Application of phased game-based education model in children with upper limb fractures (分阶段游戏式教育模式在上肢骨折儿童中的应用研究) - WEI Sen (韦森); ZHANG Yaoyao (张摇摇); HU Yanwen (胡彦文); CHEN Qiongmei (陈琼玫); DAI Shenyin (代声银) (Association of Integrative Nursing, 2023)
Objective To　construct and evaluate a health education program suitable for the physical and mental characteristics and disease characteristics of children with fracture. Methods A phased health education program was designed according to the theory of play therapy and health education, and main content of education program included: ① Relationship building stage; ② Exploration and perception stage; ③Comprehension and interpretation stage; ④Education and cognitive formation stage. Different game goals and projects were designed at each stage to promote the realization of children's rehabilitation goals. Totally 80 children with upper limb fractures were randomly divided into experimental group and control group, with 40 cases in each group. The experimental group adopted the phased game-based rehabilitation scheme and the control group adopted the conventional rehabilitation scheme. The joint mobility and exercise compliance were measured compared between the two groups. Results The score of Fugl-Meyer Assessment increased in both groups after intervention, and score of Fugl-Meyer Assessment in the study group was higher than that in the control group(P＜0. 01). The exercise compliance rate in the study group was higher than that in the control group (95. 00% vs. 75. 00%, P<0. 05). Conclusion The application of phased game-based education model in hospitalized children with upper limb fractures can effectively reduce their psychological and physiological pressure and improve their compliance with rehabilitation exercise and rehabilitation effect. (目的 以游戏作为载体, 构建适合骨折患儿身心特点和疾病特点的健康教育方案并进行应用评价。方法 根据游戏治疗理论和健康教育理论设计分阶段健康教育方案。方案内容: ①建立关系阶段; ②探索与感知阶段; ③领悟与解释阶段; ④教育与认知形成阶段。在各阶段设计不同的游戏目标和项目, 以促进患儿康复目标的实现。将80例上肢骨折儿童随机分为研究组和对照组, 每组40例。研究组采用分阶段游戏式康复方案, 对照组采用常规康复方案, 比较两组患儿伤肢关节活动度、锻炼依从性、健康教育效果的差异。结果 治疗后, 两组Fugl-Meyer评分升高, 且观察组患儿的Fugl-Meyer评分高于对照组, 差异有统计学意义(P＜0. 01)。观察组锻炼依从性95. 00%(38/40 ), 高于对照组的75. 00%(30/40), 差异有统计学意义(P＜0. 05)。结论 分阶段游戏式教育模式在上肢骨折住院儿童的应用能有效减少患儿心理和生理上压力, 提高儿童康复锻炼的依从性以及康复效果。)